Interpreting Quranic Rhetorical Questions As Indirect Speech Acts: Part-I - Ahmed, Dr. Muhammad Asif Gul , Mr. Riaz (Migration Letters, 2024)
This study presents a qualitative analysis of a set of rhetorical questions in the Holy Quran. The data set consists of 33 rhetorical questions that start with exactly same syntactic phrase. Considering rhetorical questions as indirect speech acts, the illocutionary force of each question in the data set has been explored and it has been shown that they perform a variety of illocutionary acts depending on their context, addressee and content. About their interconnection in engendering readers’ emotional involvement that heightens their psychological impact and argumentative effect, it was also found that the set shared several similarities. Minor differences were also visible.